Between Legal Mandate and Political Bargaining: How Pokok Pikiran Fund Is Understood in Aceh’s Budgeting Process - Farhana, Intan; Biizni Putri Bengi (Global Financial Accounting Journal, 2025)
This study investigates how Pokok Pikiran (pokir) fund, Indonesia’s aspiration fund scheme, is understood and practised in Aceh’s provincial budgeting process. Adopting an interpretive qualitative case study, the research draws on semi-structured interviews with members of parliament, executive budget officials, and civil society actors, complemented by analysis of media reports. The data were thematically coded to capture how different stakeholders justify, contest, and negotiate the role of pokir. The findings show that pokir is narrated in multiple and sometimes contradictory ways: as a legal mandate, as a channel for representing community aspirations, and as a bargaining instrument embedded in budget politics. While defended as a mechanism of responsiveness, its implementation often results in project personalisation, delays, and blurred boundaries between legislative and executive responsibilities. This study argues discretionary allocations such as pokir should not be seen simply as indication of weak governance. Rather, they reflect the fragility of accountability infrastructures, where limited transparency, weak monitoring, and institutionalised political practices allow the continued contestation of the scheme to persist. Addressing pokir therefore requires strengthening the broader accountability system. this research highlights the need for reforms that not only enhance monitoring and transparency, but also address the informal bargaining practices that shape allocations such as pokir.. For academics, this study contributes to public sector accounting by budgeting operates as a social practice where narratives of responsibility are performed and strategically used in political bargaining.